PENGARUH PENGALAMAN KERJA, PROMOSI JABATAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. BHUMIADYA INDONESIA BANDUNG - DRAJAT SULISTIYONO DRAJAT SULISTIYONO (POLITEKNIK PIKSI GANESHA, 2019)
This study aims to determine and analyze the effect of work experience, job promotions, and work motivation to influence the performance of employees at PT. Bhumiadya Indonesia, Padalarang. Analysis of the influence of variables using multiple regression analysis with simple random techniques. The results of the study illustrate that all variables have less influence on employee performance except the compensation variable. The results of this study can be a reference for various parties to improve employee performance. For this reason, attention needs to be paid to work experience in the organization. Besides that, it is also necessary to continuously develop employee through promotion of position and motivation towards employees.